Если g(z)=\frac{z}{-5}−5,1, то g(−4) = .

Кристина01012004 Кристина01012004    2   04.12.2021 14:12    0

Ответы
Аня3885 Аня3885  19.01.2022 05:12

g(z)=\dfrac{z}{-5}-5.1

Вместо z подставим число (-4):

g(-4)=\dfrac{-4}{-5}-5.1=\dfrac{4}{5}-5.1=0.8-5.1=-4.3

ответ: -4.3

ПОКАЗАТЬ ОТВЕТЫ
sharshukovauly sharshukovauly  19.01.2022 05:12
Подставляем значение аргумента "-4" в функцию "g(z)=\dfrac{z}{-5}-5,1" ⇒ \bf~g(-4)=\dfrac{-4}{-5} -5,1=\dfrac{4}{5} -5,1=0,8-5,1=\boxed{\bf-4,3} .ОТВЕТ: -4,3.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра